The life cycle theory and permanent income theory in household financial sustainability - Siti Nur Aqilah Ab Wahab; Minah Japang; Lee, Hock Ann; Nur Shahirah Azman (Faculty of Economics and Muamalat, Universiti Sains Islam Malaysia, 2024)
This article explains the interplay between the Life Cycle Theory (LCT) and Permanent Income Theory (PIT) in the domain of household financial sustainability. By integrating these two prominent frameworks, it offers a comprehensive approach to understanding how households manage their financial activities across their lifetimes. Considering the criticisms of both consumption theories, the article aims to provide valuable insights into distinct aspects of household personal sustainable finance, particularly in the areas of debt management and repayment, assessing sustainable consumption behavior, household expenditure and investment patterns, as well as the utilization and reduction of debt. Integrating these two theories presents a more holistic understanding of household financial sustainability.